La recherche-création en design, corps chercheur et corps créateur - Tremblay-Laliberté, Marie (RACAR : Revue d'art canadienne / Canadian Art Review, 2025)
Through an exploration of the embodied dimension of design research-creation, and highlighting its links with phenomenology and pragmatism, this article focuses on the role of the body as subject in this research practice in order to highlight the value of its outputs and to emphasize the aesthetic qualities thereof as vectors of knowledge that provide ways of enriching the epistemological field of design from within the discipline itself. To demonstrate the role played by the body and its importance in design research-creation through practice, the work of Montreal-based researcher-creator Katherine Lapierre will be addressed through the Villa Tekhnai project (2021–2023).